PEMBATALAN PEMINANGAN DAN AKIBAT HUKUMNYA DITINJAU DARI HUKUM ISLAM DAN ADAT ACEH (STUDI KASUS DI KECAMATAN PIDIE-SIGLI, NAD - NIDA DESIANTI (PREMISE LAW JURNAL, 2015)
Proposing in Arabic is called ‘khitbah’ which is the notification of the intention of a man to get married with a certain woman and the woman side tells about it to her wali. When she and her family agree, she and the man are bound and legal implication has been effective between them. In the Islamic law, it is said that proposal and engagement can be called as a legal domicile since a woman who has been engaged cannot be proposed by another man, for the proposal has moral implication. In Aceh community, especially in Aceh Pidie community that is mostly Moslems, there are still many people who perform proposal and engagement before getting married. Engagements can end with marriages, but many of them end without marriages which mean that one of the parties cancels the proposal. In Aceh Pidie, when one of the parties cancels the proposal, customary sanction will be imposed on them. Keywords: Proposal Cancelling, Islamic Law, Aceh Custom